A kind of recycled concrete and preparation method thereof

By using a combination technology of mixed protective particles of paraffin, quicklime and silica fume in recycled concrete, the problem of steel bar debris corrosion in recycled concrete is solved, and the structural stability and compressive strength are significantly improved.

CN116425495BActive Publication Date: 2025-01-14SHANGHAI CAIYUAN NEW WALL MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310285120.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-22
Publication Date
2025-01-14
Estimated Expiration
2043-03-22

AI Technical Summary

Technical Problem

Rebar debris in recycled concrete is prone to rust in tiny cracks, resulting in damage to the concrete structure. The existing magnetic separation methods cannot effectively remove the cracks, drumming and peeling caused by them.

Method used

Mixed protective particles formed by mixing paraffin, quicklime and silica fume are embedded in the tiny cracks of the regenerated aggregate, and melted and covered the steel bar debris through hydration and heat, combining quicklime and silica fume to produce gel repair substances to prevent corrosion. At the same time, silicone emulsion and nanotubes are used to form a membrane structure to isolate moisture and fill cracks to prevent rust.

Benefits of technology

Effectively prevent steel bar debris corrosion, improve the structural stability and compressive strength of recycled concrete, and reduce the risk of structural damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004139507410000051
    Figure BDA0004139507410000051
  • Figure BDA0004139507410000061
    Figure BDA0004139507410000061
  • Figure BDA0004139507410000091
    Figure BDA0004139507410000091
Patent Text Reader

Abstract

The present application relates to the field of recycled concrete, and specifically discloses a recycled concrete and a preparation method thereof. A recycled concrete is made of the following raw materials in parts by weight: 30-50 parts of cement; 20-30 parts of sand; 8-15 parts of fly ash; 2-6 parts of mineral powder; 25-35 parts of water; 3-5 parts of water reducer; 3-4 parts of retarder; 0.1-0.3 parts of defoamer; 100-120 parts of recycled aggregate; 4-8 parts of mixed protective particles; the mixed protective particles are mixed with paraffin, quicklime and silica fume, and the weight ratio of paraffin, quicklime and silica fume is 1: (0.3-0.6): (0.1-0.5). During the application process, the recycled concrete of the present application can effectively prevent the steel scraps in the deep micro-cracks of the recycled aggregate from rusting, thereby ensuring that it maintains excellent structural stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of recycled concrete, and more specifically, to recycled concrete and a preparation method thereof. Background Art

[0002] With the acceleration of urbanization in modern society, waste concrete is increasing day by day. A large amount of construction waste cannot be effectively treated and natural aggregate resources are becoming increasingly exhausted. Recycled concrete can effectively treat construction waste and solve the problem of decreasing aggregates. Modification of recycled aggregates and the use of reasonable recycled concrete preparation technology can solve the problems existing in the application of recycled concrete and have irreplaceable ecological benefits.

[0003] Recycled concrete refers to the new concrete made by crushing, cleaning, grading, mixing with grading in a certain proportion, partially or completely replacing natural aggregates such as sand and gravel, and then adding cement, water, etc. The disintegrated concrete is crushed and screened into coarse and fine aggregates, which are used to replace part of the natural aggregates to make concrete, that is, recycled concrete, which can save natural mineral resources and reduce the pollution of solid waste to the environment. At present, the processing method of recycled aggregate is mainly to organically combine cutting and crushing equipment, conveying machinery, screening equipment and impurity removal equipment to complete the processes of crushing, screening and impurity removal, and finally obtain recycled fine aggregate and recycled coarse aggregate that meet the quality requirements.

[0004] With respect to the above-mentioned related technologies, the inventors believe that during the processing of recycled aggregate, steel bar fragments will be generated during the removal of steel bars. Usually, the recycled aggregate needs to be magnetically separated before use to remove the steel bar fragments mixed in the recycled aggregate. However, a large number of microcracks are accumulated inside the concrete due to damage during the crushing process, and some steel bar fragments are deposited in the tiny cracks and cannot be effectively removed by magnetic separation operations. As a result, when the recycled aggregate is used in the preparation of concrete, the steel bar fragments are prone to rust in the tiny cracks. The rusted steel bar fragments will cause damage to the concrete structure, and then easily cause cracking, bulging and peeling. Therefore, it is urgent to propose a solution to solve the above-mentioned technical problems. Summary of the invention

[0005] In order to prevent the concrete structure from being damaged due to rust of steel bar fragments in tiny cracks of recycled aggregate, the present application provides a recycled concrete and a preparation method thereof.

[0006] In the first aspect, the present application provides a recycled concrete, which adopts the following technical solution:

[0007] A recycled concrete is made from the following raw materials in parts by weight:

[0008] 30-50 parts of cement;

[0009] 20-30 parts of sand;

[0010] 8-15 parts of fly ash;

[0011] 2-6 parts of mineral powder;

[0012] 25-35 parts water;

[0013] 3-5 parts of water reducing agent;

[0014] 3-4 parts of retarder;

[0015] Defoaming agent 0.1-0.3 parts;

[0016] 100-120 parts of recycled aggregate;

[0017] Mix 4-8 parts of protective particles;

[0018] The mixed protective particles are prepared by mixing paraffin wax, quicklime and silica fume, and the weight ratio of the paraffin wax, quicklime and silica fume is 1:(0.3-0.6):(0.1-0.5).

[0019] By adopting the above technical scheme, the main raw material of the mixed protective particles is paraffin, which is soft in texture and can be easily embedded in the tiny cracks of the recycled aggregate during the preparation of concrete. It melts under the action of the hydration heat generated during the concrete curing process, enters deep into the tiny cracks, and then covers the remaining steel debris, thereby effectively preventing the steel debris from rusting. Quicklime and silica fume can produce gel repair substances during the application of concrete, which can repair the tiny cracks of the recycled aggregate, and then after the concrete is cured, it can well prevent the outside air and water from entering the tiny cracks, and can effectively prevent the steel debris remaining in the deep of the tiny cracks from rusting. At the same time, when paraffin, quicklime and silica fume are mixed as mixed protective particles, they can play an excellent composite synergistic role with each other, and can fully fill the tiny cracks of the recycled aggregate during the curing process of the concrete, effectively preventing the steel debris from rusting, and the formed mixed matrix has excellent stability during the application process, thereby greatly reducing the possibility of harm caused by the rusting of steel debris during the application of the recycled mixed concrete after curing, which is conducive to maintaining the stability of the overall structure.

[0020] Preferably, the weight ratio of the paraffin wax, quicklime and silica fume is 1:0.4:0.3.

[0021] By adopting the above technical scheme, the mixed protective particles formed by mixing paraffin, quicklime and silica fume in the above proportions have the most excellent and stable effect during the application process. They can not only effectively penetrate into the tiny cracks to cover the residual steel debris, but also stably fill and repair the tiny cracks of the recycled aggregate, thereby greatly reducing the possibility of rusting of the steel debris, and making the recycled concrete have excellent structural stability after solidification and application.

[0022] Preferably, 5-10 parts by weight of a functional additive are added to the raw materials of the recycled concrete, and the functional additive consists of an organic silicon emulsion and nanotubes, and the weight ratio of the organic silicon emulsion to the nanotubes is (3-8):1.

[0023] By adopting the above technical scheme, the addition of silicone emulsion can form a membrane structure on the surface of recycled aggregate, which can effectively isolate the infiltrated moisture and make the steel scraps less likely to rust; the nanotubes can fill the tiny cracks on the recycled aggregate, which can not only protect the steel scraps from rusting, but also enhance the structural density of the recycled concrete; at the same time, the silicone emulsion and the nanotubes are used as functional additives, which can play an excellent compounding and synergistic role with each other. By utilizing the pipeline effect of the nanotubes, the silicone emulsion can be effectively transported to the deep of the tiny cracks of the recycled aggregate, and a membrane protection structure with nanotubes as the skeleton can be formed in the deep of the tiny cracks, which can effectively prevent the steel scraps from rusting, which is beneficial to ensure that the structural stability of the recycled concrete during the curing application process is greatly improved.

[0024] Preferably, the weight ratio of the silicone emulsion to the nanotubes is 5:1.

[0025] By adopting the above technical scheme, the silicone emulsion and nanotubes in the above weight ratio have a relatively excellent coordination effect during the application process, and can form a relatively stable and continuous skeleton membrane protection structure during the application process, which has an excellent isolation and protection effect on the steel fragments deep in the tiny cracks of the recycled aggregate, making the steel fragments less likely to rust, thereby enabling the recycled concrete to maintain excellent and stable structural strength during the curing application process.

[0026] Preferably, the nanotubes are one or a combination of carbon nanotubes, titanium dioxide nanotubes, silicon nanotubes and titanate nanotubes.

[0027] By adopting the above technical scheme, the above types of nanotubes have good dispersibility, have an excellent filling effect on the tiny cracks of the recycled aggregate, and can cooperate with the silicone emulsion to play a stabilizing role, making it difficult for the steel fragments deep in the tiny cracks to rust, thereby ensuring that the recycled concrete has excellent structural stability during the application process.

[0028] Preferably, the nanotubes are titanate nanotubes.

[0029] By adopting the above technical solution, the specific surface area of ​​titanate nanotubes is large, and they can be stably filled into the tiny cracks of recycled aggregates. The high porosity of titanate nanotubes is more conducive to cooperating with silicone emulsions and conducting silicone emulsions deep into the tiny cracks. At the same time, titanate nanotubes have many surface active sites, which can stably act as a skeleton and adhere more closely to the membrane structure formed by silicone emulsions, thereby being able to play an outstanding and excellent role in isolating and protecting steel debris, making the steel debris in the tiny cracks of recycled aggregates less likely to rust, and ensuring the structural stability of recycled concrete during application.

[0030] Preferably, the water reducer is any one of a lignin sulfonate water reducer, a naphthalene sulfonate water reducer, a melamine water reducer and a polycarboxylate water reducer.

[0031] By adopting the above technical scheme, the above-mentioned types of water reducers have excellent dispersibility in various raw material mixing systems, can disperse cement particles, improve workability, reduce water consumption, and make recycled concrete have excellent fluidity, thereby being able to form a relatively uniform and stable internal structure network.

[0032] Preferably, the retarder is one or a combination of tartaric acid, citric acid, sodium gluconate, sodium tripolyphosphate and sodium pyrophosphate.

[0033] By adopting the above technical scheme, the above types of coagulants can prolong the setting speed of the recycled concrete during the application process, which is conducive to the mixed protective particles to fully and stably play their role during the application process.

[0034] Preferably, the recycled aggregate consists of recycled coarse aggregate and recycled fine aggregate in a weight ratio of (4-6):1.

[0035] By adopting the above technical solution, the recycled coarse aggregate and recycled fine aggregate in the above weight ratio can form a dense stack during the application process, thereby ensuring that the recycled concrete has a lower porosity, and can better prevent external air and water from entering the interior of the recycled concrete and contacting with steel scraps, which is beneficial to ensuring the stability of the recycled concrete during the application process.

[0036] In a second aspect, the present application provides a method for preparing recycled concrete, which adopts the following technical solution:

[0037] A method for preparing recycled concrete comprises the following steps:

[0038] (1) preparing raw materials including cement, sand, fly ash, mineral powder, water, water reducing agent, retarder, defoaming agent, recycled aggregate and mixed protective particles according to the proportion;

[0039] (2) After the recycled aggregate and the mixed protective particles in step (1) are mixed evenly, cement, sand, fly ash and mineral powder are added and mixed evenly to obtain a mixed material; water and a water reducing agent are mixed evenly to obtain an aqueous solution;

[0040] (3) The mixed material and the water agent in step (2) are mixed evenly, and a retarder and a defoamer are added during the mixing process to obtain recycled concrete.

[0041] By adopting the above technical solution, the recycled aggregate and the mixed protective particles are firstly mixed, which is conducive to embedding the mixed protective particles into the tiny cracks of the recycled aggregate and fully playing a role in the subsequent recycled concrete curing process. At the same time, the preparation steps of the recycled concrete of the present application are relatively few, the process is simple, and it is convenient for large-scale production, and the obtained recycled concrete has excellent and stable quality.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. Since the present application adopts the mixed protective particles formed by mixing paraffin, quicklime and silica fume, it can penetrate deep into the tiny cracks of the recycled aggregate, form isolation protection for the steel debris, and effectively repair the tiny cracks. In the application process of concrete, it can effectively avoid the steel debris from rusting and causing greater harm, which is conducive to maintaining the stability of the overall structure;

[0044] 2. In the present application, it is preferred to use a functional additive composed of an organosilicon emulsion and nanotubes. The nanotubes can fill the tiny cracks on the recycled aggregate. By utilizing the pipeline effect of the nanotubes, the organosilicon emulsion can be effectively transported to the deep of the tiny cracks in the recycled aggregate, and a membrane protection structure with nanotubes as the skeleton can be formed in the deep of the tiny cracks, thereby effectively preventing the steel scraps from rusting, which is beneficial to greatly improve the structural stability during the application of recycled concrete. DETAILED DESCRIPTION

[0045] The present application is further described in detail below with reference to the embodiments.

[0046] Unless otherwise specified, the raw materials used in the examples of this application are commercially available:

[0047] The cement was purchased from Tianrui Cement, which is silicate cement PO.42.5;

[0048] Sand was purchased from Lincheng Minerals to process 20-40 mesh river sand for building concrete;

[0049] The fly ash was purchased from the secondary fly ash of Guangxi Hengshitong Stone Co., Ltd.

[0050] The mineral powder was purchased from Shijiazhuang Mayue Building Materials Co., Ltd. S95 grade slag powder;

[0051] The defoamer was purchased from polyether defoamer MY-9100;

[0052] Paraffin wax was purchased from Dongguan Shengbang Polymer Materials Co., Ltd. No. 40 low melting point paraffin wax, with a melting point of 37.5-42.5°C;

[0053] The particle size of recycled coarse aggregate is greater than 4.75 mm, and the particle size of recycled fine aggregate is less than 4.75 mm, both of which are provided by Beijing Antai Xiongqu Construction Engineering Co., Ltd.;

[0054] The silicone emulsion was purchased from Shin-Etsu KM-901;

[0055] Titanate nanotubes were purchased from Nanjing Xianfeng Nanomaterials Technology Co., Ltd., with diameters of 4–10 nm and lengths of 100–500 nm;

[0056] Silicon nanotubes were provided by Suzhou Beike Nanotechnology Co., Ltd., with diameters of 20-30 nm and lengths of 100-500 nm;

[0057] Titanium dioxide nanotubes were produced by Guangzhou Hongwu Material Technology Co., Ltd., with a diameter of 3-5 nm and a length of 100-500 nm;

[0058] The lignin sulfonate water reducer was purchased from Jinan Tengxu Chemical Technology Co., Ltd., which is sodium lignin sulfonate, industrial grade;

[0059] Polycarboxylate water reducer was purchased from Nanjing Xinyi Synthetic Technology Co., Ltd. with the product number CP1901X.

[0060] Example

[0061] Example 1

[0062] A recycled concrete, whose components and their corresponding weights are shown in Table 1, is prepared by the following steps:

[0063] (1) preparing raw materials including cement, sand, fly ash, mineral powder, water, water reducing agent, retarder, defoaming agent, recycled aggregate and mixed protective particles according to the proportion;

[0064] (2) After the recycled aggregate and the mixed protective particles in step (1) are mixed evenly, cement, sand, fly ash and mineral powder are added and mixed evenly to obtain a mixed material; water and a water reducing agent are mixed evenly to obtain an aqueous solution;

[0065] (3) The mixed material and the water agent in step (2) are mixed evenly, and a retarder and a defoamer are added during the mixing process to obtain recycled concrete.

[0066] Note: In the above steps, the mixed protective particles are mixed with paraffin, quicklime and silica fume, and the weight ratio of paraffin, quicklime and silica fume is 1:0.4:0.3; the water reducer is lignin sulfonate water reducer; the retarder is sodium tripolyphosphate; the recycled aggregate is composed of recycled coarse aggregate and recycled fine aggregate in a weight ratio of 5:1.

[0067] Example 2-3

[0068] A recycled concrete, which is different from Example 1 in that the components and their corresponding weights are shown in Table 1.

[0069] Table 1 Components of recycled concrete in Examples 1-3 and their weight parts (kg / part)

[0070]

[0071]

[0072] Example 4

[0073] A recycled concrete, which is different from Example 1 in that the mixed protective particles are prepared by mixing paraffin wax, quicklime and silica fume in a weight ratio of 1:0.3:0.1.

[0074] Example 5

[0075] A recycled concrete, which is different from Example 1 in that the mixed protective particles are prepared by mixing paraffin wax, quicklime and silica fume in a weight ratio of 1:0.6:0.5.

[0076] Example 6

[0077] A recycled concrete, which is different from Example 1 in that the mixed protective particles are prepared by mixing paraffin wax, quicklime and silica fume in a weight ratio of 1:0.45:0.3.

[0078] Example 7

[0079] A recycled concrete, which is different from Example 1 in that the water reducer is a polycarboxylate water reducer.

[0080] Example 8

[0081] A recycled concrete, which is different from Example 1 in that the retarder is a composition of sodium gluconate and sodium pyrophosphate in a weight ratio of 1:1.

[0082] Example 9

[0083] A recycled concrete, which is different from Example 1 in that the recycled aggregate consists of recycled coarse aggregate and recycled fine aggregate in a weight ratio of 4:1.

[0084] Example 10

[0085] A recycled concrete, which is different from Example 1 in that the recycled aggregate consists of recycled coarse aggregate and recycled fine aggregate in a weight ratio of 6:1.

[0086] Embodiment 11

[0087] A recycled concrete, which is different from Example 1 in that step (3) is specifically configured as follows: the mixed material and the water agent in step (2) are uniformly mixed, and a retarder, a defoamer and 7.5 parts by weight of a functional additive are added during the mixing process, wherein the functional additive is composed of an organic silicon emulsion and nanotubes in a weight ratio of 5:1, and the recycled concrete can be obtained. The nanotubes used are titanate nanotubes.

[0088] Example 12

[0089] A recycled concrete, which is different from Example 11 in that the weight portion of the functional additive added is 5 parts.

[0090] Embodiment 13

[0091] A recycled concrete, which is different from Example 11 in that the weight portion of the functional additive added is 10 parts.

[0092] Embodiment 14

[0093] A recycled concrete, which is different from Example 11 in that the functional additive consists of silicone emulsion and nanotubes in a weight ratio of 3:1.

[0094] Embodiment 15

[0095] A recycled concrete, which is different from Example 11 in that the functional additive consists of silicone emulsion and nanotubes in a weight ratio of 8:1.

[0096] Example 16

[0097] A recycled concrete, which is different from Example 11 in that the functional additive consists of silicone emulsion and nanotubes in a weight ratio of 5.5:1.

[0098] Embodiment 17

[0099] A recycled concrete, which is different from Example 11 in that the nanotubes used are silicon nanotubes.

[0100] Embodiment 18

[0101] A recycled concrete, which is different from Example 11 in that the nanotubes used are a composition of titanium dioxide nanotubes and titanate nanotubes in a weight ratio of 1:1.

[0102] Embodiment 19

[0103] A recycled concrete, which is different from Example 11 in that the functional additive is an organosilicon emulsion.

[0104] Embodiment 20

[0105] A recycled concrete, which is different from Example 11 in that the functional additive is nanotubes.

[0106] Embodiment 21

[0107] A recycled concrete, which is different from Example 11 in that the functional additive consists of silicone emulsion and nanotubes in a weight ratio of 2.5:1.

[0108] Embodiment 22

[0109] A recycled concrete, which is different from Example 11 in that the functional additive consists of silicone emulsion and nanotubes in a weight ratio of 8.5:1.

[0110] Comparative Example

[0111] Comparative Example 1

[0112] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain paraffin.

[0113] Comparative Example 2

[0114] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain quicklime.

[0115] Comparative Example 3

[0116] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain silica fume.

[0117] Comparative Example 4

[0118] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain paraffin and quicklime.

[0119] Comparative Example 5

[0120] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain paraffin wax and silica fume.

[0121] Comparative Example 6

[0122] A recycled concrete, which is different from Example 1 in that the mixed protective particles do not contain quicklime and silica fume.

[0123] Comparative Example 7

[0124] A recycled concrete, which is different from Example 1 in that the component raw materials do not contain mixed protective particles.

[0125] Comparative Example 8

[0126] A recycled concrete, which is different from Example 1 in that the mixed protective particles are mixed with paraffin, quicklime and silica fume in a weight ratio of 1:0.2:0.05.

[0127] Comparative Example 9

[0128] A recycled concrete, which is different from Example 1 in that the mixed protective particles are prepared by mixing paraffin wax, quicklime and silica fume in a weight ratio of 1:0.7:0.6.

[0129] Performance test samples: Before use, the recycled aggregate was mixed with steel chips purchased from Wei Keju Steel Chips-41 model, and then magnetic separation was performed to remove the steel chips. During the process, a small amount of steel chips would enter deep into the tiny cracks of the recycled aggregate and could not be removed by magnetic separation; at this time, the weight ratio of the recycled aggregate to the residual steel chips was 100:1.

[0130] Then, the recycled concrete obtained by using the above recycled aggregate in Examples 1-22 was used as test samples 1-22; and the recycled concrete obtained by using the above recycled aggregate in Comparative Examples 1-9 was used as control samples 1-9.

[0131] Test method: Test samples 1-22 and control samples 1-9 are made into standard specimens according to the requirements of GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", with ten standard specimens corresponding to each sample.

[0132] Take 5 standard specimens corresponding to each sample, test the compressive strength according to the requirements of GB / T50081-2002 "Standard Test Method for Mechanical Properties of Ordinary Concrete", and take the average value corresponding to each sample as the initial compressive strength value.

[0133] Five standard specimens corresponding to each type of sample are placed in the same environment with an ambient temperature of 45°C, a relative humidity of 45%, and a carbon dioxide concentration of 20%; a salt solution is prepared in a ratio of 1L deionized water and 30g sodium chloride salt, and half of the volume of the standard specimen is immersed in the salt solution, and the other half is placed in the above environment; after a 28-day placement test, the compressive strength is tested in accordance with the requirements of GB / T50081-2002 "Standard Test Method for Mechanical Properties of Ordinary Concrete", and the average value corresponding to each sample is recorded as the compressive strength experimental value.

[0134] Finally, the compressive strength loss rate of the test samples 1-22 and the control samples 1-9 was calculated, where the compressive strength loss rate = (initial compressive strength value - experimental compressive strength value) / initial compressive strength value, and the lower the compressive strength loss rate, the more stable the structure of the recycled concrete.

[0135] Table 2 Test results of test samples 1-22 and control samples 1-9

[0136]

[0137]

[0138] It can be seen from the combination of Examples 1-3 and Comparative Examples 1-7 and Table 2 that the mixed protective particles formed by mixing paraffin, quicklime and silica fume can exert a good anti-corrosion effect during the experiment, effectively preventing the steel scraps in the deep micro-cracks of the recycled aggregate from rusting, and thus making the experimentally measured compressive strength loss rate lower. At the same time, the use of any one or two of paraffin, quicklime and silica fume has limited effects, and only superposition of effects between each other, while the combination of the three raw materials can play a role in compounding and synergizing. It can be seen from the combination of Examples 4-6 and Comparative Examples 8-9 and Table 2 that the weight ratio of paraffin, quicklime and silica fume in the mixed protective particles is 1: (0.3-0.6): (0.1-0.5), which can play an excellent compounding and synergizing role, and when it is lower than or exceeds the above range, it can only bring about the superposition of simple effects between each other. Among them, when the weight ratio of paraffin, quicklime and silica fume is 1: 0.4: 0.3, the overall effect is the most excellent, and the experimentally measured compressive strength loss rate is the lowest.

[0139] Combining Example 1 and Example 11-16 and Table 2, it can be seen that the use of the functional additive composed of the organosilicon emulsion and the nanotubes can further reduce the compressive strength loss rate of the recycled concrete measured by the experiment, indicating that the functional additive has played an outstanding role in preventing the corrosion of steel scraps, wherein when the weight ratio of the organosilicon emulsion and the nanotubes is 5:1, the improvement effect is the most excellent. Combining Example 19-20 and Table 2, it can be seen that the use of any one of the organosilicon emulsion and the nanotubes as a functional additive alone has limited improvement effects, and the sum of the improvement effects brought by each is far less than the excellent improvement effect brought by the compounding of the two, indicating that the coordination between the organosilicon emulsion and the nanotubes has outstanding and significant progress. Combining Example 19-20 and Table 2, it can be seen that when the weight ratio of the organosilicon emulsion and the nanotubes is lower or higher than (3-8):1, the excellent improvement effect brought by the compounding of the two within the range cannot be achieved. Finally, it can be seen from Example 11 and Examples 17-18 that the functional additive can only play an excellent role when the nanotubes are titanate nanotubes, while the use of other types of nanotubes, or the use of titanate nanotubes in combination with other types of nanotubes, cannot achieve the outstanding effect brought by the use of titanate nanotubes alone.

[0140] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A recycled concrete, characterized in that: Made from the following raw materials in parts by weight: 30-50 parts of cement; 20-30 parts of sand; 8-15 parts of fly ash; 2-6 parts of mineral powder; 25-35 parts water; 3-5 parts of water reducing agent; 3-4 parts of retarder; Defoaming agent 0.1-0.3 parts; 100-120 parts of recycled aggregate; Mix 4-8 parts of protective particles; The mixed protective particles are made of paraffin wax, quicklime and silica fume, and the weight ratio of paraffin wax, quicklime and silica fume is 1: (0.3-0.6): (0.1-0.5); The raw materials of the recycled concrete are further added with 5-10 parts by weight of a functional additive, which is composed of an organic silicon emulsion and nanotubes, and the weight ratio of the organic silicon emulsion to the nanotubes is (3-8):

1.

2. The recycled concrete according to claim 1, characterized in that: The weight ratio of the paraffin wax, quicklime and silica fume is 1:0.4:0.

3.

3. The recycled concrete according to claim 1, characterized in that: The weight ratio of the organic silicon emulsion to the nanotubes is 5:

1.

4. The recycled concrete according to claim 1, characterized in that: The nanotubes are one or a combination of carbon nanotubes, titanium dioxide nanotubes, silicon nanotubes and titanate nanotubes.

5. The recycled concrete according to claim 4, characterized in that: The nanotubes are titanate nanotubes.

6. The recycled concrete according to claim 1, characterized in that: The water reducer is any one of a lignin sulfonate water reducer, a naphthalene sulfonate water reducer, a melamine water reducer and a polycarboxylate water reducer.

7. The recycled concrete according to claim 1, characterized in that: The retarder is one or a combination of tartaric acid, citric acid, sodium gluconate, sodium tripolyphosphate and sodium pyrophosphate.

8. The recycled concrete according to claim 1, characterized in that: The recycled aggregate consists of recycled coarse aggregate and recycled fine aggregate in a weight ratio of (4-6):

1.

9. The method for preparing recycled concrete according to claim 1, characterized in that: The following steps are involved: (1) Prepare raw materials including cement, sand, fly ash, mineral powder, water, water reducer, retarder, defoamer, recycled aggregate, mixed protective particles and functional additives according to the proportion; (2) After the recycled aggregate and the mixed protective particles in step (1) are mixed evenly, cement, sand, fly ash and mineral powder are added and mixed evenly to obtain a mixed material; water and a water reducing agent are mixed evenly to obtain an aqueous solution; (3) The mixed material and the water agent in step (2) are mixed evenly, and a retarder, a defoamer and a functional additive are added during the mixing process to obtain recycled concrete.

Citation Information

Patent Citations

  • Recycled concrete and preparation method thereof

    CN112876153A